2-O-alpha-D-glucosyl-L-ascorbic acid potassium salt crystal and preparation method thereof

By adding alcohol to the aqueous potassium hydroxide solution, new potassium salt crystals of ascorbic acid 2-glucoside were successfully prepared, which solved the problem of lack of new crystal forms in the prior art, achieved widespread application in various fields, and had flexible pH adjustment capabilities.

CN119751523APending Publication Date: 2025-04-04NAGASE MICRO BIOTECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411931102.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-02-20
Filing Date
2020-02-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The lack of novel crystal forms of ascorbic acid 2-glucoside in the prior art limits its wide application in various fields.

Method used

The potassium salt crystals of ascorbic acid 2-glucoside were successfully precipitated by dissolving ascorbic acid 2-glucoside in a specific concentration of aqueous potassium hydroxide, adding alcohol and letting stand. The crystal was confirmed as a completely new crystal form by HPLC analysis and powder X-ray diffraction.

Benefits of technology

New potassium salt crystals of ascorbic acid 2-glucoside are provided, which can adjust the pH range of its aqueous solution without using alkali neutralization, and are suitable for the manufacture of food, cosmetics, medical external products, medicines, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751523A_ABST
    Figure CN119751523A_ABST
Patent Text Reader

Abstract

The invention relates to a potassium salt crystal of 2-O-alpha-D-glucosyl-L-ascorbic acid and a preparation method of the potassium salt crystal. The present invention addresses the problem of providing a novel crystal of 2-O-alpha-D-glucosyl-L-ascorbic acid and a method for producing the same, and provides a crystal of a potassium salt of 2-O-alpha-D-glucosyl-L-ascorbic acid and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

This application is a divisional application of Chinese patent application No. 202080028448.8 with the same invention name. The original international application number is PCT / JP2020 / 004590, and the international application date is February 6, 2020. Technical Field

[0001] The present invention relates to novel potassium salt crystals of 2-O-α-D-glucosyl-L-ascorbic acid and a preparation method thereof. Background Art

[0002] 2-O-α-D-glucosyl-L-ascorbic acid (hereinafter referred to as "ascorbic acid 2-glucoside" in this specification) is a compound obtained by bonding one molecule of D-glucose to the 2-hydroxyl group of the L-ascorbic acid (vitamin C) molecule via an α-glycosidic bond. Unlike L-ascorbic acid, ascorbic acid 2-glucoside is non-reducing and has excellent stability, so it is also called "stable vitamin C". In addition, ascorbic acid 2-glucoside is easily enzymatically hydrolyzed into L-ascorbic acid and D-glucose in the body, exerting the physiological activity inherent to L-ascorbic acid.

[0003] Ascorbic acid 2-glucoside is produced on an industrial scale by reacting a solution containing starch and L-ascorbic acid with cyclomaltodextrin-glucosyltransferase (hereinafter referred to as "CGTase" in the present specification) and then with glucoamylase (for example, see Patent Documents 1 to 3, etc.). A powder containing high-purity ascorbic acid 2-glucoside in anhydrous form is sold by the present applicant under the trade name "AA2G" (registered trademark) in the fields of cosmetics and quasi-drugs, and is widely used in the fields of cosmetics and quasi-drugs, mainly as a whitening ingredient, etc. In addition, a powder containing ascorbic acid 2-glucoside in anhydrous form for food and beverages is also sold by the present applicant under the trade name "ASCOFRESH" (registered trademark) (for example, see Patent Documents 4 to 7, etc.).

[0004] Regarding ascorbic acid 2-glucoside, various other crystal forms other than the above-mentioned anhydrous crystals have also been reported. For example, patent document 8 discloses hydrous crystals of ascorbic acid 2-glucoside. In addition, in patent document 9, as crystals of metal salts of ascorbic acid 2-glucoside, two crystalline powders of aluminum salt of ascorbic acid 2-glucoside and crystalline powder of zinc salt of ascorbic acid 2-glucoside are disclosed. Furthermore, patent document 10 discloses hydrous crystals and anhydrous crystals of sodium salt of ascorbic acid 2-glucoside. However, crystals of ascorbic acid 2-glucoside other than these have not been reported. If new crystals of ascorbic acid 2-glucoside or its salt can be provided, it is very useful in terms of expanding the use options of ascorbic acid 2-glucoside in various fields. Prior art literature

[0005] Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 3-139288 Patent Document 2: Japanese Patent Application Laid-Open No. 3-135992 Patent Document 3: Japanese Patent Application Laid-Open No. 3-183492 Patent Document 4: Japanese Patent Application Laid-Open No. 4-046112 Patent Document 5: Japanese Patent Application Laid-Open No. 4-182412 Patent Document 6: Japanese Patent Application Laid-Open No. 4-182413 Patent Document 7: Japanese Patent Application Laid-Open No. 4-182419 Patent Document 8: Japanese Patent No. 5856963 Patent Document 9: Japanese Patent No. 3290490 Patent Document 10: Japanese Patent No. 6307444 Summary of the invention Problems to be solved by the invention

[0006] The present invention aims to provide a novel crystal of a salt of ascorbic acid 2-glucoside and a method for preparing the same. Means of solving problems

[0007] In order to solve the above-mentioned problems, the present inventors, etc., in the process of various studies on the crystallization conditions of ascorbic acid 2-glucoside, found that ascorbic acid 2-glucoside was dissolved in a potassium hydroxide aqueous solution of a specific concentration, and alcohol was added and allowed to stand, and as a result, crystals were precipitated. The obtained crystals were subjected to HPLC analysis, and as a result, only the peak of ascorbic acid 2-glucoside was confirmed, and the powder X-ray diffraction method was subjected to the powder X-ray diffraction pattern, which was different from the crystals of ascorbic acid 2-glucoside known in the past, was used, and it was determined to be a new crystal of ascorbic acid 2-glucoside. Furthermore, since the crystals contain a specific amount of potassium and water, it is determined to be a hydrated crystal of potassium salt. Moreover, the present inventors, etc. clearly defined the physical properties of the potassium salt crystals of the new ascorbic acid 2-glucoside, and established its preparation method, thereby completing the present invention.

[0008] That is, the present invention solves the above-mentioned problems by providing novel potassium salt crystals of ascorbic acid 2-glucoside and a method for producing the same. Effects of the Invention

[0009] According to the present invention, novel potassium salt crystals of ascorbic acid 2-glucoside can be provided. When the potassium salt crystals of ascorbic acid 2-glucoside of the present invention are used together with anhydrous crystals of ascorbic acid 2-glucoside to form a mixture, by appropriately adjusting the mixing ratio of the two, the aqueous solution of the mixture can be adjusted to a desired pH range without using an alkali to neutralize the strongly acidic ascorbic acid 2-glucoside, and thus can be advantageously used in the production of food and beverages, cosmetics, quasi-drugs, pharmaceuticals, industrial products, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is an optical microscope photograph (magnification 125 times) of crystals obtained by adding methanol to an aqueous solution of ascorbic acid 2-glucoside in potassium hydroxide. Figure 2 This is a powder X-ray diffraction pattern of crystals obtained by adding methanol to an aqueous solution of ascorbic acid 2-glucoside in potassium hydroxide. Figure 3 Yes Figure 2 The powder X-ray diffraction pattern of the shown crystals is compared with the powder X-ray diffraction patterns of anhydrous crystals, hydrous crystals and sodium salt crystals (hydrous crystals) of ascorbic acid 2-glucoside. Figure 4 This is an ORTEP image of a crystalline solid of potassium ascorbic acid 2-glucoside obtained by single crystal X-ray structure analysis. DETAILED DESCRIPTION

[0011] The present invention relates to a potassium salt crystal of ascorbic acid 2-glucoside. The potassium salt crystal of ascorbic acid 2-glucoside of the present invention is not limited to a crystal produced by a specific production method as long as it is a crystal of a novel salt of ascorbic acid 2-glucoside independently discovered by the present inventors, is a crystal of potassium salt of ascorbic acid 2-glucoside, and exhibits the physical properties and characteristics of the potassium salt crystal of ascorbic acid 2-glucoside disclosed in this specification.

[0012] As shown in the experimental items described later, the potassium salt crystals of ascorbic acid 2-glucoside of the present invention are characterized in that, in a powder X-ray diffraction pattern obtained by a powder X-ray diffraction method using CuKα rays as an X-ray source, characteristic diffraction peaks are shown at least at diffraction angles (2θ) of 8.27°, 8.81°, 16.05°, 18.88°, and 25.64°. This powder X-ray diffraction pattern is different from the powder X-ray diffraction patterns of the anhydrous crystals, hydrated crystals, and sodium salt crystals of the conventionally known ascorbic acid 2-glucoside, and therefore the crystals obtained in the present invention are crystals of ascorbic acid 2-glucoside that are different from the conventionally known ascorbic acid 2-glucoside crystals.

[0013] In addition, as shown in the experimental items described later, the potassium salt crystals of ascorbic acid 2-glucoside of the present invention generally show a water content of 12.5 to 14.8% by mass when measured by the Karl-Fischer method using a conventional method. This shows that the potassium salt crystals of ascorbic acid 2-glucoside of the present invention are in a crystalline form.

[0014] The potassium salt crystals of ascorbic acid 2-glucoside of the present invention generally contain 14.1 to 14.6 mass % of potassium when measured by ion chromatography in the experimental items described below. From this result, it can be confirmed that the potassium salt crystals of ascorbic acid 2-glucoside of the present invention are potassium salt crystals.

[0015] Incidentally, the present inventors have also succeeded in obtaining a single crystal having a size capable of analyzing the single crystal X-ray crystal structure of a hydrated crystal of potassium ascorbic acid 2-glucoside. As shown in the experimental item described later, the single crystal, according to the X-ray crystal structure analysis, is an orthorhombic system, and has a space group of P212121 and a lattice constant of of crystals.

[0016] In addition, the present invention provides a novel method for preparing a crystal of potassium salt of ascorbic acid 2-glucoside. The method for preparing a crystal of potassium salt of ascorbic acid 2-glucoside of the present invention comprises: dissolving ascorbic acid 2-glucoside as a raw material in a potassium hydroxide aqueous solution of a specific concentration, then adding a specific amount of alcohol, and leaving the mixture to stand at a low temperature to precipitate crystals, and then recovering the crystals by a solid-liquid separation method such as centrifugal separation, thereby producing a crystal of potassium salt of ascorbic acid 2-glucoside containing water.

[0017] In the production of ascorbic acid 2-glucoside potassium salt containing crystals, the ascorbic acid 2-glucoside as a raw material can be obtained by organic synthesis regardless of its source. However, it is usually suitable to use a conventionally known method for producing ascorbic acid 2-glucoside for food, beverages and cosmetics, that is, a solution containing ascorbic acid 2-glucoside obtained by a method in which starch and L-ascorbic acid are allowed to react with CGTase and then with glucoamylase, or a quasi-drug grade ascorbic acid 2-glucoside anhydrous crystal powder prepared therefrom (trade name "AA2G" (registered trademark), ascorbic acid 2-glucoside purity 98% or more, sold by Hayashibara Co., Ltd.), or a food grade ascorbic acid 2-glucoside anhydrous crystal powder (trade name "ASCOFRESH" (registered trademark), ascorbic acid 2-glucoside purity 98% or more, sold by Hayashibara Co., Ltd.).

[0018] When ascorbic acid 2-glucoside is used as a raw material to produce potassium salt crystals of ascorbic acid 2-glucoside, for example, a potassium hydroxide aqueous solution having a concentration of 4 to 8 equivalents (N) is added and dissolved at a ratio of 2 liquid volume to the mass of anhydrous crystals of ascorbic acid 2-glucoside, and then an alcohol is added and mixed at a ratio of 3 or more liquid volume, and then the mixture is left to stand at low temperature, so that the water-containing crystals of potassium salt of ascorbic acid 2-glucoside are precipitated. Specifically, for example, when 1 g of anhydrous crystals of ascorbic acid 2-glucoside is used, 2 mL of a potassium hydroxide aqueous solution having a concentration of 4 to 8 equivalents (N) is added and dissolved therein, and then 3 mL or more of alcohol is added and mixed, and the mixture is left to stand at low temperature. The molar ratio of potassium hydroxide to ascorbic acid 2-glucoside is usually preferably 2.7 to 5.4, and more preferably in the range of 3.4 to 4.1. In addition, the alcohol added in the operation of precipitating the crystals is not particularly limited, and methanol and ethanol commonly used in the field can be suitably used. The alcohol concentration during crystallization is preferably about 50% by volume in terms of final concentration. The precipitated crystals can be recovered by a common solid-liquid separation method such as filtration or centrifugation.

[0019] The hydrous crystals of potassium ascorbate 2-glucoside obtained by the crystallization operation can be washed with an alcohol aqueous solution to obtain hydrous crystals of higher purity. The hydrous crystals obtained can be crushed and dried as needed to obtain a powder containing crystalline solids of potassium ascorbate 2-glucoside. Alternatively, a powder containing crystalline solids of potassium ascorbate 2-glucoside can be obtained by spray drying a sugar mass obtained by adding alcohol to precipitate crystals.

[0020] As one of the characteristics of the hydrous crystals of the potassium salt of ascorbic acid 2-glucoside of the present invention, it can be mentioned that when dissolved in water, the obtained aqueous solution shows alkalinity, which is the same as the crystals of the sodium salt of ascorbic acid 2-glucoside known in the art. In contrast to the properties, when the anhydrous crystals of ascorbic acid 2-glucoside are dissolved in water, the obtained aqueous solution shows strong acidity. Therefore, the new hydrous crystals of the potassium salt of ascorbic acid 2-glucoside created by the present inventors can be suitably used even in applications where the amount, form of use, and use itself are limited due to the strong acidity of the aqueous solution of the anhydrous crystals of ascorbic acid 2-glucoside in the past. For example, when using a soap-based skin external composition requiring weak alkalinity, such as soap, shampoo, facial cleanser, body wash, etc., when using a conventional powder containing anhydrous crystalline ascorbic acid 2-glucoside, it is necessary to neutralize the acidic solution of ascorbic acid 2-glucoside dissolved in an aqueous medium with an alkali in advance and to add a buffer for adjusting the pH. However, since an aqueous solution obtained by dissolving hydrous crystals of ascorbic acid 2-glucoside potassium salt generally exhibits alkalinity, when it is formulated in the skin external composition, it is often unnecessary to neutralize ascorbic acid 2-glucoside with an alkali and it is also unnecessary to use a buffer in combination.

[0021] Furthermore, when the hydrous crystals of potassium ascorbate 2-glucoside and the anhydrous crystals of ascorbate 2-glucoside are used together, by adjusting the mixing ratio of the two, the following advantages can be obtained: an aqueous solution of ascorbate 2-glucoside having a pH within a predetermined range, for example, a range from weakly alkaline to weakly acidic when dissolved in an aqueous medium can be obtained. Therefore, when the hydrous crystals of potassium ascorbate 2-glucoside and the anhydrous crystals of ascorbate 2-glucoside are used together, the following advantages can be obtained: various compositions including skin external compositions and basic cosmetics can be produced in which the overall pH is preferably within a range from weakly alkaline to weakly acidic without using a base other than the hydrous crystals of potassium ascorbate 2-glucoside to neutralize ascorbate 2-glucoside. In addition, when both are used in combination, when preparing various compositions, it is sufficient to measure the anhydrous crystals of ascorbic acid 2-glucoside and the hydrous crystals of ascorbic acid 2-glucoside potassium salt in the amounts according to their respective mixing ratios, but it is convenient to prepare a composition in which anhydrous crystals of ascorbic acid 2-glucoside and hydrous crystals of ascorbic acid 2-glucoside potassium salt are mixed in a predetermined mass ratio according to the pH required for the target composition. In this case, the mass ratio can be arbitrarily set according to the desired pH, but in order to make it into a weakly acidic to neutral range commonly used in cosmetic applications, it is usually suitable to mix in a mass ratio of 70:30 to 45:55, preferably 50:50 to 45:55.

[0022] The crystals of potassium ascorbate 2-glucoside of the present invention are novel crystal forms of ascorbate 2-glucoside, and are similar to the crystals of sodium ascorbate 2-glucoside in that the pH of their aqueous solutions show alkalinity. The crystals of potassium ascorbate 2-glucoside of the present invention can be advantageously used in the manufacture of foods and beverages, cosmetics, quasi-drugs, pharmaceuticals, or industrial products containing ascorbate 2-glucoside, similar to the anhydrous crystals, hydrated crystals, sodium salt crystals, etc., of ascorbate 2-glucoside known in the past.

[0023] Hereinafter, the present invention will be described in detail through experiments.

[0024] <Experiment 1: Preparation of new crystals of ascorbic acid 2-glucoside> 12 g of a commercially available powder containing anhydrous ascorbic acid 2-glucoside (trade name "ASCO FRESH" (registered trademark), sold by Hayashihara Co., Ltd.) was dissolved in 24 mL of a 5N potassium hydroxide aqueous solution, and then 36 mL of methanol was further added to the aqueous solution and stirred. The solution was left to stand at 4°C for 4 days, and white turbidity was observed. The precipitation of crystals was confirmed by microscopic observation. The crystal suspension was filtered using a Kiriyama funnel (using Toyo filter paper No. 5), and the crystals were recovered. After washing with deionized water, the crystals were vacuum dried at 30°C for 5 hours to obtain about 15.4 g of a crystalline powder. The molar ratio of potassium hydroxide to ascorbic acid 2-glucoside in the aqueous solution was 3.4.

[0025] <Experiment 2: Various analyses of new crystals of ascorbic acid 2-glucoside> The crystals obtained in Experiment 1 were observed for crystal shape under a microscope, and subjected to HPLC analysis, pH of aqueous solution, measurement of UV absorption spectrum, powder X-ray diffraction pattern, and various measurements of water content and potassium content.

[0026] <Experiment 2-1: Crystal shape> The crystals obtained in Experiment 1 were observed using an optical microscope (BX-50, manufactured by Olympus Corporation) to determine their shape. The crystals obtained in Experiment 1 were 10 to 100 μm × 1000 μm in size, columnar in shape, and transparent. A microscope photograph (magnification 125 times) of a typical crystal among the obtained crystals was taken and is shown in FIG. Figure 1 .in addition, Figure 1 The scale bar shown in the lower right is 200 μm in length.

[0027] <Experiment 2-2: HPLC analysis> The crystals obtained in Experiment 1 were dissolved in deionized water to a final concentration of 1% by mass, and HPLC analysis was performed under the following conditions. As a control, a food-grade powder containing anhydrous ascorbic acid 2-glucoside (trade name "ASCO FLEX" (registered trademark), sold by Hayashibara Co., Ltd.) was used and analyzed under the same conditions. <HPLC analysis conditions> Column: Wakopak Wakobeads T-330, (inner diameter 10 mm×length 300 mm) H-type 28901 (sold by Wako Pure Chemical Industries, Ltd.) Eluent: 0.0001N nitric acid aqueous solution Flow rate: 0.4mL / min Temperature: Room temperature Detector: Differential Refractometer

[0028] In the HPLC chromatogram of the test sample solution in which the crystals were dissolved, substantially only the peak of ascorbic acid 2-glucoside was detected, similarly to the case of the powder containing ascorbic acid 2-glucoside without crystals used as a control, and thus it was confirmed that the crystals obtained in Experiment 1 were crystals of ascorbic acid 2-glucoside.

[0029] <Experiment 2-3: pH and UV absorption spectra of aqueous solutions containing dissolved crystals> The crystals obtained in Experiment 1 were prepared into a 1 mass % aqueous solution and its pH was measured, which showed a pH of 12.7 and alkalinity. The aqueous solution was diluted 300 times and its UV absorption spectrum was measured, which showed the same UV absorption spectrum as ascorbic acid 2-glucoside (λmax 260 nm).

[0030] <Experiment 2-4: Powder X-ray Diffraction Pattern> The crystals obtained in Experiment 1 were subjected to powder X-ray diffraction analysis using a powder X-ray diffraction apparatus ("X'Pert Pro MPD", using CuKα radiation, manufactured by Spectris). About 50 mg of the crystal sample was placed on a silicon non-reflective plate and irradiated with CuKα radiation under the following conditions while rotating, and a powder X-ray diffraction pattern was obtained by the reflection method. The obtained powder X-ray diffraction pattern is shown in Figure 2 . <CuKα ray irradiation conditions> X-ray tube current: 40mA X-ray tube voltage: 45kv wavelength:

[0031] In addition, the powder X-ray diffraction pattern of the newly obtained crystals was compared with the powder X-ray diffraction pattern of the known crystals of ascorbic acid 2-glucoside. Figure 1 And recorded in Figure 3 .exist Figure 3 In the figure, the symbols A, B, C and D represent the powder X-ray diffraction pattern of the crystals obtained in Experiment 1, the powder X-ray diffraction pattern of the sodium salt crystals of ascorbic acid 2-glucoside (hydrous crystals, manufactured by Hayashibara Co., Ltd.), the powder X-ray diffraction pattern of the hydrous crystals of ascorbic acid 2-glucoside (manufactured by Hayashibara Co., Ltd.), and the powder X-ray diffraction pattern of the anhydrous crystals of ascorbic acid 2-glucoside (trade name "ASCO FRESH" (registered trademark), sold by Hayashibara Co., Ltd.), respectively.

[0032] like Figure 2 As shown, the newly obtained crystals showed characteristic diffraction peaks at diffraction angles (2θ) of 8.27°, 8.81°, 16.05°, 18.88° and 25.64° in the powder X-ray diffraction pattern ( Figure 2symbols a, b, c, d and e), except for Figure 3 It can be seen that the powder X-ray diffraction pattern is completely different from any of the powder X-ray diffraction patterns of the conventionally known anhydrous crystals, hydrated crystals and sodium salt crystals (hydrated crystals) of ascorbic acid 2-glucoside. From this result, it can be seen that the crystals obtained in Experiment 1 are novel crystals of ascorbic acid 2-glucoside.

[0033] <Experiment 2-5: Determination of water content> The water content of the crystals obtained in Experiment 1 was measured using a Karl Fischer moisture meter (trade name "AQ-2200", manufactured by Hiranuma Sangyo Co., Ltd.) and was found to be 14.8% by mass. This result shows that the new crystals of ascorbic acid 2-glucoside obtained in Experiment 1 are in the form of crystalline solids.

[0034] <Experiment 2-6: Determination of potassium content> 150 mg of the crystals obtained in Experiment 1 were weighed, dissolved in 100 mL of deionized water, and further diluted 50 times with deionized water to prepare a measurement sample. The potassium content in the sample was measured using an ion chromatograph ("DIONEX ICS-5000+", manufactured by Thermo Fisher Scientific) under the following conditions. <Measurement conditions> Column: Dionex IonPac CS16 (5×250 mm) (manufactured by Thermo Fisher Scientific) Guard column: Dionex IonPac CS16 Guard (5×50 mm) (manufactured by Thermo Fisher Scientific) Eluent: 30 mM methanesulfonic acid Flow rate: 1.0mL / min Column temperature: 40°C Detector: Conductivity detector Suppressor: Electric field regeneration type CERS-500 Current: 89mA Testing room temperature: 20℃ Sample injection volume: 25 μL Standard solution: Cation mixed standard solution II (6 types) No. 07197-96 for IC (manufactured by Kanto Chemical Co., Ltd.)

[0035] The potassium content of the crystals calculated based on the results of ion chromatography was 14.2% by mass. From this result, it was confirmed that the crystals of ascorbic acid 2-glucoside obtained in Experiment 1 were potassium salt crystals.

[0036] Incidentally, the composition (mass %) of the crystal calculated assuming that potassium exists as potassium hydroxide (KOH) in the crystal is shown in Table 1. Furthermore, the result of calculating the molar ratio of ascorbic acid 2-glucoside to potassium hydroxide in this case is also shown in Table 1.

[0037] [Table 1]

[0038] As described above, the potassium content in the hydrous crystals of potassium salt of ascorbic acid 2-glucoside is about 14.2% by mass. When it is assumed that all potassium exists in the form of potassium hydroxide (KOH), the potassium hydroxide content is calculated to be 20.4% by mass. At this time, when the mass of water (14.8% by mass) and the mass of potassium hydroxide (20.4% by mass) are subtracted from the mass of the crystal (100% by mass), the amount of ascorbic acid 2-glucoside is 64.8% by mass. The molar ratio of ascorbic acid 2-glucoside to potassium hydroxide is calculated from this value, as shown in Table 1, and is 1.0:1.90. Therefore, when it is assumed that all potassium exists in the form of potassium hydroxide, the hydrous crystals of potassium salt of ascorbic acid 2-glucoside are estimated to contain about 2 molecules of potassium hydroxide per 1 molecule of ascorbic acid 2-glucoside.

[0039] Similarly, the water content in the water-containing crystals of ascorbic acid 2-glucoside potassium salt is about 14.8% by mass, and the molar ratio of ascorbic acid 2-glucoside to water molecules is about 1.0:4.3. Therefore, it is estimated that the water-containing crystals of ascorbic acid 2-glucoside potassium salt contain 4 molecules of crystal water per 1 molecule of ascorbic acid 2-glucoside.

[0040] Judging from the results of Experiments 2-1 to 2-6, the new crystals of ascorbic acid 2-glucoside obtained in Experiment 1 were hydrous crystals of ascorbic acid 2-glucoside potassium salt.

[0041] <Experiment 3: Study on the conditions for forming potassium salt crystals of ascorbic acid 2-glucoside> 2 mL of 1 to 10 N potassium hydroxide aqueous solution shown in Table 2 below was added to 1 g of powder containing anhydrous ascorbic acid 2-glucoside crystals (trade name "ASCO FRESH" (registered trademark), sold by Hayashibara Co., Ltd.), and after dissolution, 3 mL of methanol was added and mixed, and the mixture was left at 4° C. for 24 hours, and the degree of crystal precipitation was visually observed. The degree of crystal precipitation was judged in the following four levels, and the results are shown in Table 2. “-”: No crystals were precipitated “+”: A small amount of crystals precipitated “++”: Crystals precipitate at about half the volume of the mixed solution “+++”: All crystals are precipitated and solidified

[0043] As shown in Table 2, the powder of ascorbic acid 2-glucoside anhydrous crystals was dissolved in potassium hydroxide aqueous solutions of 4N, 5N, 6N and 8N concentrations, and the precipitation of potassium salt crystals of ascorbic acid 2-glucoside was observed from the potassium hydroxide aqueous solution to which methanol was added. When the molar ratio of potassium hydroxide to ascorbic acid 2-glucoside was discussed, the precipitation of crystals was observed in the range of 2.7 to 5.4. On the other hand, when the potassium hydroxide concentration was 3N or less and the molar ratio of potassium hydroxide to ascorbic acid 2-glucoside was discussed, when the molar ratio was 2.0 or less, no crystal precipitation was observed. In addition, when the potassium hydroxide concentration was 10N or more and the molar ratio of potassium hydroxide to ascorbic acid 2-glucoside was discussed, when the molar ratio was 6.8 or more, no crystal precipitation was observed at all, and the sample was colored.

[0044] In addition, Patent Document 10 discloses a method for preparing sodium salt crystals of ascorbic acid 2-glucoside, according to which crystal precipitation is observed when the molar ratio of sodium hydroxide to ascorbic acid 2-glucoside is 1.7 or more and the amount of methanol to 1 g of ascorbic acid 2-glucoside is 1 mL. The present inventors tried to produce crystals of potassium salt of ascorbic acid 2-glucoside under the same precipitation conditions as those of sodium salt crystals disclosed in Patent Document 10 except that sodium hydroxide was first replaced with potassium hydroxide, but potassium salt crystals could not be obtained. That is, 10 mL of 8N potassium hydroxide aqueous solution was added to 10 g of powder containing anhydrous ascorbic acid 2-glucoside crystals (trade name "AA2G" (registered trademark), sold by Hayashihara Co., Ltd.), and after dissolution, 10 mL of methanol was added and mixed, and the mixture was left to stand at 4°C for 24 hours, but potassium salt crystals could not be obtained. As a result of repeated trial and error, unexpectedly, by increasing the amount of methanol added to 3 times, potassium salt crystals of ascorbic acid 2-glucoside were successfully precipitated. In summary, the potassium salt crystals of ascorbic acid 2-glucoside of the present invention are obtained under conditions completely different from those of the sodium salt crystals.

[0045] <Experiment 4: pH of the complex of ascorbic acid 2-glucoside potassium salt crystals and ascorbic acid 2-glucoside anhydrous crystals> A commercially available powder containing anhydrous crystals of ascorbic acid 2-glucoside (trade name "ASCO FRESH" (registered trademark), sold by Hayashibara Co., Ltd.) and hydrous crystals of ascorbic acid 2-glucoside potassium salt obtained by the method of Experiment 1 were mixed at a mass ratio of 100:0 to 0:100 as shown in Table 3 below, and each mixture was dissolved in deionized water to a concentration of 1 mass %, and the pH of the obtained aqueous solution was measured. The results are shown in Table 3.

[0046] [Table 3]

[0047] As shown in Table 3, the pH of a 1% by mass aqueous solution of a powder containing anhydrous crystals of ascorbic acid 2-glucoside dissolved alone (100% by mass) was 2.2, while the pH of a 1% by mass aqueous solution of a 1% by mass aqueous solution of a 100% by mass aqueous solution of potassium salt of ascorbic acid 2-glucoside dissolved alone (100% by mass) was 12.7. In addition, when the relative ratio of the powder containing anhydrous crystals of ascorbic acid 2-glucoside to the hydrous crystals of potassium salt of ascorbic acid 2-glucoside was changed in the range of 90:10 to 10:90, the pH of the 1% by mass aqueous solution showed a range of 2.5 to 12.6. From these results, it can be seen that when a powder containing anhydrous crystals of ascorbic acid 2-glucoside and hydrous crystals of ascorbic acid 2-glucoside potassium salt are mixed in an appropriate mass ratio to prepare an aqueous solution, a desired pH can be obtained in a wide range from acidic to alkaline. In particular, when the mass ratio is 70:30 to 45:55, the pH can be adjusted in the range of pH 3.0 to 7.0, and more preferably, when the mass ratio is 50:50 to 45:55, the pH can be adjusted in the range of weakly acidic to neutral pH 4.4 to 7.0.

[0048] <Experiment 5: Hygroscopicity of crystals containing potassium ascorbic acid 2-glucoside> The hydrated crystals of potassium ascorbate 2-glucoside obtained by the method of Experiment 1 and the hydrated crystals of sodium ascorbate 2-glucoside obtained by the method of Patent Document 10 were compared in terms of their hygroscopicity. Specifically, 0.5 g of each of the hydrated crystals of potassium ascorbate 2-glucoside and the hydrated crystals of sodium ascorbate 2-glucoside were weighed and stored in a desiccator at room temperature with a saturated saline solution to a relative humidity (RH) of 75.2% for 24 hours. The mass of each was measured, and the mass increase due to moisture absorption was calculated, and the mass increase rate {(mass increase due to storage / mass at the start of storage) × 100} (mass %) was calculated. The results are shown in Table 4.

[0049] [Table 4] Samples to be tested <![CDATA[Mass increase rate * (mass%)]]> Ascorbic acid 2-glucoside potassium salt hydrate crystals 9.1 Ascorbic acid 2-glucoside sodium salt hydrate crystals 15.8 *: Relative humidity 75.2%, room temperature, after 24 hours of storage

[0050] As shown in Table 4, the mass increase rates of the hydrous crystals of potassium ascorbate 2-glucoside and sodium ascorbate 2-glucoside in this test were 9.1 mass % and 15.8 mass %, respectively, and it was determined that both of them absorbed moisture under the condition of relative humidity (RH) 75.2%. The mass increase rate of the hydrous crystals of potassium ascorbate 2-glucoside was less than 60% of the mass increase rate of the hydrous crystals of sodium ascorbate 2-glucoside, and it was found that the hygroscopicity of the hydrous crystals of potassium ascorbate 2-glucoside was lower than that of the hydrous crystals of sodium ascorbate 2-glucoside.

[0051] <Experiment 6: Single crystal X-ray crystal structure analysis of crystalline solid of potassium salt of ascorbic acid 2-glucoside> In order to obtain relatively large crystals that can be used for single crystal X-ray crystal structure analysis, crystallization is carried out under conditions that are more difficult to precipitate than normal crystals. That is, 1g of powder containing anhydrous crystals of ascorbic acid 2-glucoside (trade name "Ascorbic Flux" (registered trademark), sold by Hayashihara Co., Ltd.) is dissolved in 2mL of 4N potassium hydroxide aqueous solution with a concentration lower than that of normal crystallization, and then 3mL of methanol is added for mixing, and crystallization is carried out for 4 days to precipitate water-containing crystals of ascorbic acid 2-glucoside potassium salt. Crystals of appropriate size (0.30×0.09×0.07mm) are selected from the obtained crystals, and an X-ray diffraction device ("RIGAKU VariMax with Saturn 724", manufactured by Rigaku Co., Ltd.) is used to measure the X-ray diffraction pattern under the following conditions. The analysis software uses "Crystal Clear" (manufactured by Rigaku Co., Ltd.). <Measurement conditions> Incident X-rays: MoKα rays (wavelength ) Output: 50kv, 24mA Detector: Imaging plate Measuring temperature: about -173℃ (nitrogen blowing method)

[0052] In the X-ray diffraction pattern on the imaging plate, many diffraction spots were observed, confirming that the crystal was a single crystal. The crystallographic parameters of the crystalline solid of potassium ascorbate 2-glucoside obtained by single crystal X-ray crystal structure analysis are summarized in Table 5.

[0053] [Table 5]

[0054] According to the obtained X-ray diffraction intensity data, as shown in Table 5, it is determined that the hydrated crystals of ascorbic acid 2-glucoside potassium salt belong to the orthorhombic system, the space group is P212121, and the lattice constant is

[0055] In addition, based on the obtained X-ray diffraction intensity data, it is believed that the molecular formula of the crystalline form of potassium salt of ascorbic acid 2-glucoside is C 12 H 24 K2O 15 , the structural formula is C 12 H 17 O 11 - 2K + OH - ·3H2O, molecular weight is 486.51. Figure 4 As shown, the crystal is estimated to contain the following components: 1 molecule of ascorbic acid 2-glucoside obtained by dissociation of hydrogen from the 3-hydroxyl group of L-ascorbic acid, 2 potassium ions, 1 hydroxide ion, and 3 water molecules. Example

[0056] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples. Example 1

[0057] <Hydrated crystals of ascorbic acid 2-glucoside potassium salt> 1 kg of a commercially available powder containing anhydrous crystals of ascorbic acid 2-glucoside (trade name "AA2G" (registered trademark), purity 98% by mass or more, sold by Hayashibara Co., Ltd.) was added to 2 L of a 5N potassium hydroxide aqueous solution and completely dissolved by stirring. 3 L of methanol was added to the aqueous solution and mixed, and 10 g of hydrous crystals of ascorbic acid 2-glucoside potassium salt prepared in advance by the method of Experiment 1 was added as seed crystals, stirred and mixed, and then left at 5° C. for 3 days to precipitate crystals. Then, the obtained crystals were collected by filtration, washed with a 60% by volume methanol aqueous solution, and dried at 30° C., thereby producing about 1.1 kg of hydrous crystals of ascorbic acid 2-glucoside potassium salt. The purity of ascorbic acid 2-glucoside in the present crystals was measured by the HPLC method described in Experiment 2-2 and was found to be 99.2% by mass. The water content was measured by the Karl Fischer method and was found to be 12.5% ​​by mass. The potassium content of the crystals calculated based on the results of ion chromatography was found to be 14.1% by mass.

[0058] This product is a hydrous crystal product of potassium ascorbate 2-glucoside with good fluidity. It can be widely used in various compositions such as food, cosmetics, quasi-drugs, and pharmaceuticals. Example 2

[0059] <Crystal-containing powder containing ascorbic acid 2-glucoside potassium salt> 7 parts by mass of cassava starch were added to 25 parts by mass of water, a commercially available liquefying enzyme was added, and after heating and dissolving, 3 parts by mass of L-ascorbic acid was added, and the pH was adjusted to 5.5 to prepare a matrix solution. 100 units of CGTase from Geobacillus stearothermophilus were added per 1 g of cassava starch solid matter, and the mixture was reacted at 55° C. for 50 hours to generate ascorbic acid 2-glucoside and ascorbic acid 2-glycoside.

[0060] The reaction solution was heated to inactivate the enzyme, and then the pH was adjusted to 4.5. 50 units of glucoamylase (trade name "Guluco #20000", 20,000 units / g, sold by Nagase Chem Tech Co., Ltd.) were added per 1 g of starch solids, and the reaction was carried out at 55° C. for 24 hours to decompose ascorbic acid 2-glycoside into ascorbic acid 2-glucoside and decompose the mixed sugar into glucose. The content of ascorbic acid 2-glucoside in the reaction solution was about 30.5% by mass in terms of anhydrous content.

[0061] The reaction solution was heated to inactivate the enzyme, decolorized with activated carbon and filtered, and the filtrate was filtered with a cation exchange resin (H + Then, L-ascorbic acid and ascorbic acid 2-glucoside were adsorbed on an anion exchange resin (OH - Type), washed with water to remove most of the glucose, eluted with 0.5N hydrochloric acid solution, concentrated, and then used for strong acid cation exchange resin (trade name "ダウエツクス 50WX4", Ca 2+ The ascorbic acid 2-glucoside-rich fraction was recovered by gel permeation chromatography (Dow Chemical Co., Ltd.). The composition of the recovered ascorbic acid 2-glucoside-containing solution was 95.3% by mass of ascorbic acid 2-glucoside, 1.2% by mass of L-ascorbic acid, 2.5% by mass of glucose, and 1.0% by mass of others, calculated on an anhydrous basis.

[0062] The solution containing ascorbic acid 2-glucoside was concentrated under reduced pressure to a solid matter concentration of about 60% by mass, potassium hydroxide was added to a final concentration of 5N to dissolve it, and ethanol was added to a final concentration of 60% by volume. The solution was collected in a crystallization tank, cooled to 5°C, and 2% by mass of the hydrous crystal powder of ascorbic acid 2-glucoside potassium salt obtained by the method of Experiment 1 was added as a seed crystal relative to the solid matter mass of ascorbic acid 2-glucoside, and gently stirred and crystallized for 3 days to obtain a sugar paste in which hydrous crystals of ascorbic acid 2-glucoside potassium salt were precipitated. The sugar paste was recovered by a basket centrifuge by a conventional method, and the crystals were washed by spraying a small amount of 75% by volume ethanol aqueous solution, and then pulverized and dried to obtain a powder containing crystalline solids of ascorbic acid 2-glucoside potassium salt. The purity of ascorbic acid 2-glucoside of this product was 98.6% by mass as converted to anhydrous substance. The water content was measured by Karl Fischer method and found to be 14.3% by mass. The potassium content of the crystals calculated based on the result of ion chromatography was 14.1% by mass.

[0063] This product is a powder product containing crystals of potassium ascorbic acid 2-glucoside with good fluidity. It can be widely used in various compositions such as food, cosmetics, quasi-drugs, and medicines. Example 3

[0064] <Complex of hydrated crystals of potassium salt of ascorbic acid 2-glucoside and anhydrous crystals of ascorbic acid 2-glucoside> 50 parts by mass of a powder containing anhydrous crystals of ascorbic acid 2-glucoside potassium salt (trade name "AA2G" (registered trademark), sold by Hayashibara Co., Ltd.) was uniformly mixed with 50 parts by mass of the hydrous crystals of ascorbic acid 2-glucoside potassium salt obtained by the method of Example 1, pulverized and dried to obtain a powdery complex.

[0065] This product is a complex of hydrous crystals of potassium salt of ascorbic acid 2-glucoside and general-purpose anhydrous crystals of ascorbic acid 2-glucoside, and can be advantageously used as a raw material for cosmetics, as well as for quasi-drugs, medicines, foods, etc., as with conventional powders containing anhydrous crystals of ascorbic acid 2-glucoside. In addition, since the aqueous solution of this product exhibits weak acidity, it can be easily adjusted to a desired pH compared to the case of using conventional powders containing anhydrous crystals of ascorbic acid 2-glucoside. Example 4

[0066] <Lotion> (formula)

[0067] After dissolving the ingredients (1) to (4) of the above formulation in purified water (9), the mixture of ingredients (5) to (8) is slowly added and mixed to prepare a lotion. This product is a lotion formulated with ascorbic acid 2-glucoside, and is used as an anti-aging lotion having not only anti-wrinkle and anti-fine line effects, but also excellent whitening effects, anti-spot and anti-sagging effects, and effects of maintaining or enhancing the skin barrier function and hyaluronic acid production. In addition, since 1,2-pentanediol is formulated, it is a lotion having excellent antiseptic effect and moisturizing properties, low irritation to the skin, and excellent stability. Example 5

[0068] <Beauty Essence> (formula)

[0069] According to the above formulation, the ingredients are mixed by a conventional method to prepare a beauty serum. This product is a beauty serum formulated with ascorbic acid 2-glucoside, and is used as an anti-aging beauty serum that exerts stable anti-wrinkle and anti-fine line effects, has excellent whitening effects, and has excellent feeling during use. Example 6

[0070] <Health supplements> 1 part by mass of the complex obtained by the method of Example 3 and 99 parts by mass of trehalose (trade name "トレハ" (trade name "Treha") (registered trademark), sold by Hayashihara Co., Ltd.) were uniformly mixed to prepare a product filled in glass bottles of 50 g each. This product is used as a vitamin C-fortified (vitamin C-rich) health supplement food. Example 7

[0071] <Healthy Food> 85 parts by mass of skim milk, 3 parts by mass of skim milk powder, 6 parts by mass of trehalose (trade name "トレハ" (trade name "Treha") (registered trademark), sold by Hayashihara Co., Ltd.), 0.1 parts by mass of agar, 3 parts by mass of the complex obtained by the method of Example 3, 4 parts by mass of powdered sugar-transferred hesperidin and 2 parts by mass of purified water were placed in a mixing tank and heated to 55°C while stirring to completely dissolve. Then, the mixture was homogenized according to a conventional method, sterilized by a sterilizing cooler, inoculated with 3% of a starter, filled into a plastic container, and fermented at 37°C for 5 hours to obtain a yogurt-type health food. This product is a yogurt-type health food fortified with vitamin C (rich in vitamin C). Example 8

[0072] <Vitamin C powder preparation> The complex obtained by the method of Example 3 was used as a powdered food material, 70 parts by mass of sucrose, 10 parts by mass of dextrin, and an appropriate amount of spices were added thereto, and the mixture was stirred and mixed using a mixer to produce a vitamin C powder preparation. The crystalline powder of ascorbic acid 2-glucoside and other powders can be easily and uniformly mixed using a mixer, and can be produced without any obstacles in the production steps.

[0073] This product is a vitamin C powder preparation that can be easily mixed with other food and beverage ingredients and is not prone to browning or solidification even if stored for a long time. This product and the composition containing this product have the physiological function of vitamin C, so it can be taken orally to maintain the health of the skin and mucous membranes and whiten the skin. Example 9

[0074] <Ointment> 1 part by mass of sodium acetate trihydrate, 4 parts by mass of DL-calcium lactate and 10 parts by mass of glycerol were uniformly mixed, and the mixture was added to a mixture of 50 parts by mass of vaseline, 10 parts by mass of wood wax, 10 parts by mass of lanolin, 14.5 parts by mass of sesame oil, 1 part by mass of the complex obtained by the method of Example 3 and 0.5 parts by mass of peppermint oil, and further uniformly mixed to prepare an ointment.

[0075] This product can be advantageously used as a sunscreen, skin beautifying agent, whitening agent, etc. It can also be advantageously used as a healing promoter for trauma (wounds) and burns (scalds), etc. Industrial Applicability

[0076] The hydrous crystals of the potassium salt of ascorbic acid 2-glucoside of the present invention are new crystal forms of ascorbic acid 2-glucoside that have been unknown so far. When the hydrous crystals of the potassium salt of ascorbic acid 2-glucoside of the present invention are used in combination with anhydrous crystals of ascorbic acid 2-glucoside, by appropriately adjusting the ratio of the two, the pH of the product can be adjusted to a desired range without using an alkali to neutralize ascorbic acid 2-glucoside, so it can have the following advantages: food and beverages, cosmetics, quasi-drugs, medicines, industrial products, etc. can be manufactured more easily with fewer steps. The present invention has such excellent advantages and has great industrial applicability. Description of Reference Numerals

[0077] exist Figure 2 middle, ↓: Five characteristic diffraction peaks in the powder X-ray diffraction pattern of the crystal a: Diffraction peak with a diffraction angle (2θ) of 8.27° b: Diffraction peak with a diffraction angle (2θ) of 8.81° c: Diffraction peak with a diffraction angle (2θ) of 16.05° d: diffraction peak with a diffraction angle (2θ) of 18.88° e: Diffraction peak with a diffraction angle (2θ) of 25.64° exist Figure 3 middle, A: Powder X-ray diffraction pattern of the newly obtained crystals B: Powder X-ray diffraction pattern of ascorbic acid 2-glucoside sodium salt (water-containing crystals) C: Powder X-ray diffraction pattern of hydrated crystals of ascorbic acid 2-glucoside (1 / 2 containing water) D: Powder X-ray diffraction pattern of ascorbic acid 2-glucoside anhydrous crystals

Claims

A hydrous crystal of potassium salt of 1.2-O-α-D-glucosyl-L-ascorbic acid, which shows diffraction peaks at least at diffraction angles (2θ) of 8.27°, 8.81°, 16.05°, 18.88° and 25.64° in a powder X-ray diffraction pattern.

2. The method for preparing the crystalline form of potassium salt of 2-O-α-D-glucosyl-L-ascorbic acid according to claim 1, characterized in that: 2-O-α-D-glucosyl-L-ascorbic acid is dissolved in an aqueous potassium hydroxide solution so that the molar ratio of potassium hydroxide to 2-O-α-D-glucosyl-L-ascorbic acid is 3.4 to 4.1, alcohol is added to the aqueous solution and the solution is allowed to stand, and the precipitated crystals of potassium salt of 2-O-α-D-glucosyl-L-ascorbic acid are collected.

3. The method for preparing the crystalline form of potassium salt of 2-O-α-D-glucosyl-L-ascorbic acid according to claim 2, wherein: The alcohol is methanol or ethanol.

4. A composition comprising the hydrous crystals of the potassium salt of 2-O-α-D-glucosyl-L-ascorbic acid according to claim 1.

5. The composition according to claim 4, further comprising anhydrous crystals of 2-O-α-D-glucosyl-L-ascorbic acid, wherein the ratio of anhydrous crystals of 2-O-α-D-glucosyl-L-ascorbic acid to crystalline solids of potassium salt of 2-O-α-D-glucosyl-L-ascorbic acid is in the range of 70:30 to 45:55 in terms of mass ratio.

6. The composition according to claim 4 or 5, which is in the form of a food or beverage, a cosmetic, a quasi-drug, a pharmaceutical product or an industrial product.

Citation Information

Patent Citations

  • Bolster-less truck with swinger

    JP1983056963A

  • Mount structure of concrete floor panel

    JP1988007444A

  • Crystal2-o-alpha-d-glucopyranosyl-l-ascorbic acid, production and use thereof

    JP1991135992A

  • Alpha-glycosyl-l-ascorbic acid, its production and use thereof

    JP1991139288A

  • Production of substance with high content of 2-o-alpha-d-glucopyranosyl-l-ascorbic acid

    JP1991183492A